82.9k views
3 votes
Solve for k c=5/3(k-41)

User Tom Bowen
by
5.4k points

2 Answers

4 votes

Answer:

c=5/3(k-41)

multiply by 3 both sides

3c=5/3(k-41)3

in the right hand side 3 and they cancel

3c=5(k-41)

open the bracket

3c=5k-205

take -205 to the left hand side and it will become +205

3c+205=5k

its the same like this

5k=3c+205

divide by 5 both sides

5/5k=3/5c+205/5

k=3/5c+41 Answer

User Tahsmith
by
6.2k points
3 votes

Answer:

k = 3c/5 + 41

Explanation:

1. Simplify 5/3 (k - 41) to 5 (k - 41)/3

c = 5 (k - 41)/3

2. Multiply both sides by 3

c * 3 = 5 (k - 41)

3. Regroup terms

3c = 5 (k - 41)

4. Divide both sides by 5

3c/5 = k - 41

5. Add 41 to both sides

3c/5 + 41 = k

6. Switch sides

k = 3c/5 + 41

User RoboKozo
by
5.4k points